(untitled) (Praxis Educativa, 2021)
This article reports the results of the systematization of the experience named My ideas in three minutes, an activity implemented in the Maternal School course of the Bachelor’s Degree in Early Childhood Education at Universidad Autónoma de Bucaramanga, Colombia. The One minute paper technique was used to encourage students to reflect on their future role as teachers, by composing texts containing the analysis of their experiences and practices. Those documents were collected and analyzed, using Nvivo program, based on the following categories: identity as teachers and conceptual appropriation. However, during the process, some categories emerged, such as, appreciations about the educational system and others related to writing. The conclusions point out the potential of this technique for a reflexive exercise to be carried out in an agile way; besides, it promotes in the students the habit of constantly questioning themselves, making it possible for them to be more self-critical.